(untitled) (Sains Humanika, 2024)
Students’ mastery of the topic of Space in the field of Geometry is also influenced by their spatial reasoning. The use of technology such as augmented reality applications is necessary in assisting students in develop these skills through its ability to display real objects virtually that can be manipulated freely. However, the effectiveness of integrating augmented reality applications requires the implementation of suitable teaching strategies. This is because learning involving difficult concepts requires students not only to receive information directly but also to actively engage in learning activities to generate knowledge and skills. Therefore, this study aims to design an inquiry-based learning environment with the integration of augmented reality and examine its effects on students’ spatial reasoning for the topic of Space in Year Three Mathematics. This study used a pre-experimental quantitative research design involving 25 Year Three students. The purposive sampling method was used to select the school as the location of the study and convenience sampling was used to select students as the study respondents. Pre-tests and post-tests were used to measure students’ spatial reasoning after the intervention. The results of the descriptive analysis show that there is an increase in the mean score of 6.16 for students’ spatial reasoning. The results of the inferential analysis also prove that there is a significant difference in the mean score (Asymp. Sig. (2-tailed) <0.001) between the pre-test and the post-test on students’ spatial reasoning. Therefore, the results of this study have had a positive effect on students’ spatial reasoning. In conclusion, this study is expected to encourage teachers to apply 21st-century learning strategies along with the integration of appropriate technology tools to design a learning environment of Mathematics learning among primary school students.